The histology and function of the dermal armour of the aetosaur Stagonolepis olenkae Sulej, 2010 (Archosauria, Pseudosuchia) from Krasiejów (SW Poland) - Błaszczeć, Przemysław; Antczak, Mateusz (Acta Geologica Polonica, 2025)
Microscopic observations of the bone tissues of osteoderms covering an animal’s body can provide an insight into its lifestyle and ontogeny as well as reveal the function of the armour. In the case of the aetosaur Stagonolepis olenkae Sulej, 2010 from the locality of Krasiejów, to date only the paramedian osteoderms have been analysed and compared to other taxa within Pseudosuchia Zittel, 1887. This study examines ten disarticulated plates from different parts of the body of S. olenkae: paramedian, lateral, ventral and appendicular osteoderms. The armour of S. olenkae has a diploe structure composed of layers of external and basal cortex surrounding an internal cancellous core. In the basal layer of the osteoderms, bundles of Sharpey’s fibres and skeletochronological structures are present. The internal structures of the osteoderms indicate extensive remodelling processes, and the weak vascularization and bone tissues that constitute the plates – lamellar bone and parallel-fibred bone – suggest considerable mechanical resistance. Elements of the armour’s osteology adapted to distribute and reduce mechanical stress might provide confirmation of the protective function of the armour as well.
Keywords: Aetosauria; Stagonolepis; Osteoderms; Palaeohistology